Purification and properties of Manganese Superoxide Dismutase (MnSOD) from Tamarix aphylla L. - Hamzah, Nazar Abdulameer; Raheif, Eman Salman (Cellular and Molecular Biology, 2018)
Superoxide dismutase (SOD) of the Tamarix aphylla leaves were detected at optimum conditions that collected in April, May and June. Results indicated the specific activity in the crude extract reaching to 36.76 unit/ mg protein. Crude SOD was purified by several techniques, precipitation with ammonium sulfate (50–75) %, Ion exchange chromatography using DEAE-cellulose and two steps of size exclusion chromatography on sephacryl S-200 column. The obtained specific activity (310 unit/mg protein) and purification fold 7.91. The purified enzyme revealed one band by SDS-polyacrylamide gel electrophoresis with molecular mass 85.703 kDa. while 89.125 kDa by Sephacryl S-200. The optimal pH and temperature for enzyme activity were 7.5, and 50ºC respectively. EDTA, SDS and NaN3 reduced activity, contrariwise of H2O2 and KCN, pointed to the studied SOD is MnSOD. Michalis constant Km and maximum velocity Vmax values were 0.016 mM and 55.86 mM/min, respectively by using Pyrogallol as substrate. According to the results, we conclude Tamarix aphylla produce MnSOD which can have purified by serial purification techniques for better activity and characterized for further studies.